TNFα–308G/A Polymorphism as a Risk Factor for HPV Associated Cervical Cancer in Indian Population - Indu Kohaar; Nisha Thakur; Sudha Salhan; Swaraj Batra; Veena Singh; Anita Sharma; Pushpa Sodhani; B. C. Das; Debi P. Sarkar; Mausumi Bharadwaj (Cellular Oncology)
Background: Investigation of the potential association of single nucleotide polymorphisms (SNPs) at –308 G/A and –238 G/A of Tumor necrosis factor α (TNFα) with susceptibility to HPV-16 associated cervical cancer in Indian women. Methods: The study included 165 histologically confirmed cases with 45 precancer and 120 cancer patients and an equal number (165) of healthy controls with normal cervical cytology. PCR-RFLP was employed to analyze TNFα promoter polymorphisms, which were confirmed by direct sequencing. Both patients and controls were screened for Human Papillomavirus (HPV) infection. Results: The frequency of –308 A allele in TNFα was significantly higher in cases compared with control subjects (21% in cases vs. 9% in controls; p < 0.01), with an odds ratio of 2.7 (95% CI = 1.41–5.15). Also, women carrying A allele for this locus presented 3 times increased susceptibility to HPV 16 infection as evident from carrier genotype distribution between HPV positive cases and control subjects (24% in HPV positive cases vs. 9% in controls; p < 0.01; OR = 3.1; 95% CI = 1.60–6.03). No such association was found for TNFα–238 (G/A) polymorphism with the risk of development of cervical cancer. Conclusion: It suggests that SNP at –308 (G/A) of TNFα promoter may represent an increased risk for HPV infection and development of cervical cancer in Indian women.